Reimagining Everyday Life with Residential Solar Panels - Guo, Jinhong; Kinfe, Yodit (My University, 2022)
Solar panels for residential usage have been increasingly widespread in recent years with a continuing growth. Even though this renewable energy source is environmentally sustainable, it is of great importance that solar panels follow a socially sustainable path as well. The project Sun for All from RISE examined the female experience of the purchase process of solar panels. In parallel to Sun for all, this thesis is conducted, however, with an emphasis on the post-purchase process and consideration of a larger variety of users. By taking a norm-creative approach, the aim is to examine how solar panels influence everyday life and how that can be challenged. As a complement to the previous research in the area of solar panels, norm-creativity as well as domestication theory, data collection was collected from studying users and other stakeholders. With the help of the findings, the current situation of living with residential solar panels was better understood and the scaffold for the norm-creative approach to be applied in the conceptual design solution could be found. The succeeding iterative ideation-phase was extensive, with a broad variation of both physical and digital ideas, which finally settled on a booking system concept. After iterating from a user test, the final concept was presented as a solar panel booking system implemented for households in apartment buildings. This concept challenged the current lifestyle with solar panels by reversing several norms, especially in relation to the energy production monitoring behavior. With the norm-creative approach, an alternative way of living with solar panels was presented, with diverse potential to further develop on.
Keywords: solar panels, solar energy, domestication theory, social sustainability, norm-creative